Association Between Self-Reported Polycystic Ovary Syndrome with Chronic Diseases Among Emiratis: A Cross-Sectional Analysis from the UAE Healthy Future Study - Juber NF; Abdulle A; AlJunaibi A; AlNaeemi A; Ahmad A; Leinberger-Jabari A; Al Dhaheri AS; AlZaabi E; Al-Maskari F; AlAnouti F; Alsafar H; Alkaabi J; et al. (Dove Medical Press, 2023)
Nirmin F Juber,1 Abdishakur Abdulle,1 Abdulla AlJunaibi,2 Abdulla AlNaeemi,3 Amar Ahmad,1 Andrea Leinberger-Jabari,1 Ayesha S Al Dhaheri,4 Eiman AlZaabi,5 Fatma Al-Maskari,6,7 Fatme AlAnouti,8 Habiba Alsafar,9- 11 Juma Alkaabi,12 Laila Abdel Wareth,13 Mai Aljaber,14 Marina Kazim,15 Michael Weitzman,16 Mohammad Al-Houqani,17 Mohammed Hag-Ali,18 Naima Oumeziane,15 Scott Sherman,19 Syed M Shah,6 Wael Almahmeed,20 Youssef Idaghdour,1 Tom Loney,21 Omar El-Shahawy,19 Raghib Ali1,22 1Public Health Research Center, New York University Abu Dhabi, Abu Dhabi, United Arab Emirates; 2Department of Pediatrics, Zayed Military Hospital, Abu Dhabi, United Arab Emirates; 3Department of Cardiology, Zayed Military Hospital, Abu Dhabi, United Arab Emirates; 4Department of Nutrition and Health, College of Medicine and Health Sciences, UAE University, Al-Ain, United Arab Emirates; 5Department of Pathology, Sheikh Shakhbout Medical City, Abu Dhabi, United Arab Emirates; 6Institute of Public Health, College of Medicine and Health Sciences, UAE University, Al-Ain, United Arab Emirates; 7Zayed Center for Health Sciences, UAE University, Al-Ain, United Arab Emirates; 8College of Natural and Health Sciences, Zayed University, Abu Dhabi, United Arab Emirates; 9Center for Biotechnology, Khalifa University of Science and Technology, Abu Dhabi, United Arab Emirates; 10Department of Genetics and Molecular Biology, Khalifa University of Science and Technology, Abu Dhabi, United Arab Emirates; 11Department of Biomedical Engineering, Khalifa University of Science and Technology, Abu Dhabi, United Arab Emirates; 12Department of Internal Medicine, College of Medicine and Health Sciences, UAE University, Al-Ain, United Arab Emirates; 13The National Reference Laboratory, Abu Dhabi, United Arab Emirates; 14Healthpoint Hospital, Abu Dhabi, United Arab Emirates; 15Abu Dhabi Blood Bank Services, SEHA, Abu Dhabi, United Arab Emirates; 16Department of Environmental Medicine, New York University of Medicine, New York, NY, USA; 17Department of Medicine, College of Medicine and Health Sciences, UAE University, Al-Ain, United Arab Emirates; 18Faculty of Health Sciences, Higher Colleges of Technology, Abu Dhabi, United Arab Emirates; 19Department of Population Health, New York University School of Medicine, New York, NY, USA; 20Heart and Vascular Institute, Cleveland Clinic Abu Dhabi, Abu Dhabi, United Arab Emirates; 21College of Medicine, Mohammed Bin Rashid University of Medicine and Health Sciences, Dubai, United Arab Emirates; 22MRC Epidemiology Unit, University of Cambridge, Cambridge, UKCorrespondence: Nirmin F Juber, Public Health Research Center, New York University Abu Dhabi, Abu Dhabi, United Arab Emirates, Tel +971-2-6287631, Email nirmin.juber@nyu.eduPurpose: This study aimed to assess the prevalence of self-reported polycystic ovary syndrome (PCOS) among Emiratis and examine bi-directional associations of PCOS with self-reported chronic diseases, namely: diabetes, asthma, high cholesterol, and high blood pressure.Patients and Methods: A cross-sectional analysis was performed using the UAE Healthy Future Study (UAEHFS) data collected from February 2016 to April 2022 involving 1040 Emirati women aged 25- 67 years from recruitment centers in the United Arab Emirates (UAE). The bi-directional associations between self-reported PCOS and self-reported chronic diseases were evaluated by establishing temporality based on reported age-at-diagnoses. Firstly, the associations between PCOS (diagnosed at ≥ 25 years) and chronic diseases (diagnosed at < 25 years) were examined, followed by PCOS (diagnosed at < 25 years) and chronic diseases (diagnosed at ≥ 25 years). Finally, a Poisson regression under unadjusted and age-and-body mass index (BMI) adjusted models was performed to obtain the risk ratio (RR) and its 95% confidence interval (CI).Results: The prevalence of PCOS in this study was 25.9%. Those with asthma and high cholesterol diagnosed at < 25 years had increased risks of PCOS diagnosed at ≥ 25 years (RR = 1.79, 95% CI: 1.17- 2.76 for asthma; and RR = 1.61, 95% CI: 1.01- 2.59 for high cholesterol), compared to those respective healthier counterparts, after adjusting for age and BMI. No significant association was observed between PCOS diagnosed at < 25 years and respective chronic diseases diagnosed at ≥ 25 years.Conclusion: PCOS prevalence among Emirati women was high. Asthma and high cholesterol in earlier life were associated with PCOS in later life. Understanding how chronic disease conditions and PCOS are associated in bi-directional ways may improve the surveillance of chronic disease conditions among women with PCOS and may also contribute to more targeted PCOS prevention strategies.Keywords: polycystic ovary syndrome, self-reported diagnosis, epidemiology, women's health, United Arab Emirates, UAE Healthy Future Study